2010
DOI: 10.1007/s11739-010-0455-9
|View full text |Cite
|
Sign up to set email alerts
|

Personalized genomic medicine

Abstract: Personalized medicine provide to physicians a molecular makeup of each patient. Looking at the patient on this level helps the physician get a profile of the patient's genetic distinction, or mapping. By investigating this genetic profile, medical professionals are then able to select patients, and use the found information to plan out a course of treatment that is much more in step with the way their body works. Personalize medicine is a direct extension of the genomic medicine that use genetic information to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…The medical doctors, medical professional groups have identified a long back that each patient is unique. Subsequently, medical societies started speaking for many decades that it is documented the prevalence of similar diseases within close relatives and ethnic groups, a range of different drug responses with adverse effects, and various signs and symptoms often observed with the same pathological condition [8][9][10][11] . Although some notion of personalized medicine exists nearing 60 years, it first appeared in 1999 in a published manuscript [12][13][14] .…”
Section: B a Brief History Of Pmmentioning
confidence: 99%
“…The medical doctors, medical professional groups have identified a long back that each patient is unique. Subsequently, medical societies started speaking for many decades that it is documented the prevalence of similar diseases within close relatives and ethnic groups, a range of different drug responses with adverse effects, and various signs and symptoms often observed with the same pathological condition [8][9][10][11] . Although some notion of personalized medicine exists nearing 60 years, it first appeared in 1999 in a published manuscript [12][13][14] .…”
Section: B a Brief History Of Pmmentioning
confidence: 99%
“…This allowed for two key discoveries that have led to the age of genomic medicine; single nucleotide polymorphism (SNP) and the microarray analysis used to detect them [2,3]. SNPs account for about 90% of known genetic polymorphisms in the 0.9% of our genome that makes each individual unique [2].…”
Section: The Age Of Precision Medicinementioning
confidence: 99%
“…This allowed for two key discoveries that have led to the age of genomic medicine; single nucleotide polymorphism (SNP) and the microarray analysis used to detect them [2,3]. SNPs account for about 90% of known genetic polymorphisms in the 0.9% of our genome that makes each individual unique [2]. Characterization of SNPs in variegated pathologies and treatment success have associated different molecular signatures with the diagnosis, prognosis, and therapy given to individual patients.…”
Section: The Age Of Precision Medicinementioning
confidence: 99%
“…The successful mapping of the entire human genome revealed that though human genetic make-up is 99.1% identical, a small 0.9% inter-individual genetic difference causes a wide variability in physical and mental phenotypes among the human subjects. [ 16 ] This genomic variability may determine all variable health-related properties and behaviors among the people. The fact that response to a drug is different in every person or most of the diseases show variable manifestation in the bodies compared with each other proves PM medical model.…”
Section: Novel Personalized Medicinementioning
confidence: 99%
“…[ 18 ] SNPs are frequent single nucleotide changes in the DNA sequence which are predominantly common in the population, including 90% of all known polymorphisms. [ 16 18 19 ] Detection of these polymorphisms is essential to determine patient predisposition to various diseases and drug therapy responsiveness.…”
Section: Novel Personalized Medicinementioning
confidence: 99%